Erratum: Rybnikov et al. Selection for Plastic, Pathogen-Inducible Recombination in a Red Queen Model with Diploid Antagonists. Pathogens 2021, 10, 898 - Sviatoslav Rybnikov (MDPI AG, 2021)
In the original article, there was a mistake published in Figure 3 [...]